Single-cell multi-omics analysis reveals dysfunctional Wnt signaling of spermatogonia in non-obstructive azoospermia - Zeng, Shengjie; Chen, Liuxun; Liu, Xvdong; Tang, Haibin; Wu, Hao; Liu, Chuan (Frontiers in Endocrinology, 2023)
Background: Non-obstructive azoospermia (NOA) is the most severe type which lead to 1% male infertility. And Wnt signaling governs normal sperm maturation. However, the role of Wnt signaling in spermatogonia in NOA has incompletely been uncovered and upstream molecules regulating Wnt signaling remain blurred. Methods: Bulk RNA-seq of NOA were used to identify the hub gene module in NOA utilizing weighted gene co-expression network analyses (WGCNA). Single-cell RNA sequencing (scRNA-seq) of NOA were employed to explore dysfunctional signaling pathways in the specific cell type with genesets of signaling pathways. Single-cell regulatory network inference and clustering for Python (pySCENIC) analysis was applied to speculate putative transcription factors in spermatogonia. Moreover, single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) determined the regulated genes of these transcription factors. Finally, spatial transcriptomic data was used to analyze cell type and Wnt signaling spatial distribution. Results: Wnt signaling pathway was demonstrated to be enriched in the hub gene module of NOA by bulk RNA-seq. Then, scRNA-seq data revealed the downregulated activity and dysfunction of Wnt signaling of spermatogonia in NOA samples. Conjoint analyses of pySCENIC algorithm and scATAC-seq data indicated that 3 transcription factors (CTCF, AR, ARNTL) were related with activities of Wnt signaling in NOA. Eventually, spatial expression localization of Wnt signaling was identified to be in accordance with the distribution patterns of spermatogonia, sertoli cells and leydig cells. Conclusions: In conclusion, we identified downregulated Wnt signaling of spermatogonia in NOA and 3 transcription factors (CTCF, AR, ARNTL) may be involved in this dysfunctional Wnt signaling. These findings provide new mechanisms for NOA and new therapeutic targets for NOA patients.